Analisis Faktor-Faktor Kebutuhan dan Peluang Masyarakat Menjadi Nasabah di Bank Syariah Indonesia (BSI) KC Sibolga - Putri Masrifah; Nurul Jannah (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study discusses the analysis of the factors of people's needs and opportunities to become customers at Bank Syariah Indonesia (BSI) KC Sibolga. The formulation of the problem raised is "What are the factors that influence the needs of the community to become customers at Bank Syariah Indonesia?". The development of Islamic banking in Indonesia is currently progressing. This is evidenced by the number of Conventional Banks that have started to open Sharia Business Units. However, the development of Islamic banks has not been able to influence the needs of the community to become customers of Islamic banks. The purpose of this study was to determine the needs and opportunities of the community to become customers of Islamic banks. People want the results of borrowing funds from financial institutions will get big profits without having to be burdened with interest and avoid usury.